2013
DOI: 10.1007/s10140-013-1163-3
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian and tubal torsion: imaging findings on US, CT, and MRI

Abstract: Accurate diagnosis of adnexal torsion is often challenging, as clinical presentation is nonspecific and the differential for pelvic pain is broad. However, prompt diagnosis and treatment is critical to good clinical outcomes and preservation of the ovary and/or fallopian tube. Ultrasound (US) imaging is most frequently used to assess torsion. However, as computed tomography (CT) utilization in the emergency setting has increased, there are times when CT is the initial imaging test. Additionally, the nonspecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 36 publications
0
68
1
7
Order By: Relevance
“…However, one disadvantage in cross-sectional imaging of pregnant women is that contrast media are not used. Other disadvantages are the requirement for sedation with the use of contrast media in child patients and the careful use of gadolinium-based contrast media in children younger than 12 months due to renal function immaturity [9]. Therefore, an advanced imaging technique is needed for definitive diagnosis of ovarian torsion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one disadvantage in cross-sectional imaging of pregnant women is that contrast media are not used. Other disadvantages are the requirement for sedation with the use of contrast media in child patients and the careful use of gadolinium-based contrast media in children younger than 12 months due to renal function immaturity [9]. Therefore, an advanced imaging technique is needed for definitive diagnosis of ovarian torsion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the timely and correct diagnosis of ovarian torsion has a vital role in the protection of the ovaries and preserving fertility. A delayed diagnosis of ovarian torsion may cause severe morbidity, including ovarian necrosis, peritonitis, sepsis, and even death [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…MRI and CT were useful to show decreased contrast enhancement and adnexal fat stranding but they had not enough for certain diagnosis. 10 On the other hand, in another study, the diagnostic value of initial CT was found less beneficial than initial sonography. 11 The use of Doppler flow analysis on ultrasound can help to improve diagnostic accuracy but it has a high false-negative rate.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian hemorrhage, a frequent sequela of torsion, can be identified on MR imaging, especially using T1-weighted images where blood products are hyperintense. 42 Chiou and colleagues 43 found that the presence on MR imaging of pelvic fat infiltration, hematoma formation, and the lack of enhancement sign were highly associated with necrosis of the involved adnexa, requiring rapid surgical intervention.…”
Section: Ovarian Torsionmentioning
confidence: 98%
“…Normal Doppler flow can be observed in 45% to 61% of all ovarian torsion cases. 42,43 MR imaging should be performed after inconclusive US. Asymmetric enlargement of the ovary and stromal edema are well demonstrated by MR imaging, especially using T2-weighted sequences (Fig.…”
Section: Ovarian Torsionmentioning
confidence: 99%